Human genetic diversity and comparative economic development - Quamrul Ashraf; Oded Galor (Brown University, Department of Economics, 2008)
This research contributes to the understanding of human genetic diversity within a society as a significant determinant of its economic development. The hypothesis advanced and empirically examined in this paper suggests that there are socioeconomic trade-offs associated with genetic diversity within a given society. The investigation exploits an exogenous source of cross-country variation in genetic diversity by appealing to the 'out of Africa' hypothesis of human origins to empirically establish a highly statistically significant and robust non-monotonic effect of genetic diversity on development outcomes in the pre-colonial era. Contrary to theories that reject a possible role for human genetics in influencing economic development, this study demonstrates the economic significance of diversity in genetic traits, while abstaining entirely from conceptual frameworks that posit a hierarchy of such traits in terms of their conduciveness to the process of economic development.
Keywords: N10; N30; N50; O10; O50; Z10; 330; Human genetic diversity; Comparative development; Population density; Neolithic Revolution; Land productivity; Malthusian stagnation; Gesellschaft; Biodiversität; Bevölkerungstheorie; Wirtschaftswachstum; Entwicklung; Produktivität; Bevölkerungsdichte; Anthropologie